"A crime called nuclear power": The role of criminal law in addressing post-Fukushima damages. Issue 2 (June 2015) - Herber, Erik
Abstract This article examines the criminal indictment filed and other activities employed by the Fukushima Nuclear Energy Lawsuit Group, in the aftermath of the earthquake, tsunami and nuclear disaster that occurred in Japan on 11 March 2011 ("311"). The article thereby brings into focus the role played by criminal law in ascribing meaning to people's actions on and after the events of 311 – a subject that up until now has not received any scholarly attention. By examining the Japanese Prosecutors' Office response to the indictment the article furthermore contextualizes criminal law's role in the aftermath of 311 in terms of its more general characteristics as well as the legal reforms carried out in Japan in recent years. In doing so the article brings into focus striking differences in parties' views on and findings of 311 facts, as well as the limited impact of recent legal reforms on Japanese prosecution practices.